Nardo, The Fall Of The Roman Empire - Kolbaba, Tia (Teaching History: A Journal of Methods, 1999)
This short book is one of a series of "Opposing Viewpoints Digests" published by Greenhaven Press. The series aims to present "thought-provoking argument and stimulating debate" on various topics. This example succeeds admirably. It begins with "A Short History of Rome's Fall," which presents the facts and chronology of events with as little interpretation and opinion as possible. Similarly, the appendices to the book provide longer quotations from primary and secondary sources quoted briefly in the text, as well as a timeline of events, the chronology of Roman emperors, and an annotated bibliography. Between these two information sections, four explanations of Rome's fall are presented: changes in population, internal (class and religious) disunity, economic decay, and invasion and military conquest. A fifth chapter proposes that "Rome Did Not Fall in the Fifth Century." Within each chapter, three different views are presented. For example, in Chapter 1, "Changes in Population Caused Rome's Fall," the subdivisions are as follows: "Manpower Shortages Weakened the Empire," "Intermarriage Led to Rome's Fall," and "Intermarriage Played No Part in Rome's Decline and Fall." The viewpoints are summarized by Don Nardo, with ample questions from various historians. Nardo writes clearly and succinctly, and he glosses the vocabulary of his quotations in a way that should make them accessible even for students whose vocabulary is limited.